Perlindungan Hukum terhadap Rumah Sakit atas Kebocoran Data Rekam Medik Elektronik yang Dilakukan Oleh Peretas - Sidiq, M. Abdullah (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Hospitals' and the government's respective responsibilities in the event of a data breach involving patients' electronic health records are the focus of this investigation. Using both statutory and conceptual approaches, the research is normative juridical in nature. The findings indicate that: In the event that a patient's electronic medical record data is leaked, the hospital may face three types of legal responsibility. Firstly, there is civil liability, which allows the patient to sue the hospital for breach of contract or broken promise. Secondly, there is criminal liability, which is based on the principle of error and, if proven guilty, can result in fines and jail time for the hospital administrator. As controllers of patient personal data, hospitals may face administrative consequences such as fines, suspension of operations, termination of access to electronic systems, and/or removal from the PSE list (C. Administrative accountability). There are two aspects to the government's legislative safeguards for hospitals regarding the potential disclosure of patient information in electronic health records: preventative measures and punitive measures. Hospitals are safeguarded by Article 191 of Law No. 17 of 2023 on Health in the preventative protection category, whereas those involved in coercive dispute resolution face fines, sanctions, and jail time.